(untitled) (Research, Society and Development, 2022)
Introduction: Cancer is a major public health problem, and may be due to multiple factors, related to environmental, cultural, socioeconomic and lifestyle causes, to which the individual is subjected. Method: Retroactive research with data collected from DataSUS, with descriptive and bibliographic methodology, and with a quantitative and qualitative approach. Results: Females were the most affected in cases of cancer, with 56.12% (n= 282,726), aged between 50 and 64 years, with a total of 19.02% (n= 95,843). The Southeast presented 42.48% (n= 214,024), the South 25.30% (n= 127,481) of new neoplastic occurrences, the Northeast was the third most affected region by the occurrence of cancer, with a percentage of 22.01% (n=110). Regarding the ICD, we have: “C50 – Malignant neoplasm of the breast”, with 9.64% (n= 48,597); “C44 – Other malignant skin neoplasms” with a percentage of 9.43% (n= 47,524); and “C48 – Malignant neoplasm of the prostate,” accounting for 6.34% (n=31,968). The most prominent neoplastic staging were 3 and 4, with totals of, respectively, 8.68% (n= 43,763) and 8.26% (n= 41,619). The most adopted therapies in oncological cases were chemotherapy, with a percentage of 22.8% (n= 115,208), in second place, the surgical therapeutic modality is the most beloved, with a total of 20.5% (n = 103,700), and finally, radiotherapy, accounting for 8.5% (n= 43,049). Patients who received treatment within 30 days accounted for 25.7% (n=129,645), 18.71% (n=94,262) of patients who received treatment for more than 60 days.